Heading control of an autonomous underwater robot with sliding mode and backstepping techniques - Abdellilah, Hattab; Kamel, Yahiaoui (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
The variation of the parameters of the autonomous underwater robot (inertia, hydrodynamics), external disturbances, the non-linearity of the model to be controlled, and measurement errors due to the sensors are the factors that have a negative influence on the robot's trajectory following. Autonomous submarine. A control law that takes these different factors into account would be an adequate solution to this control problem. This work is a simulation study of some advanced control techniques for controlling the heading of an autonomous underwater robot. We have developed two robust command structures. One of them is based on the sliding-mode control, which is applied to the considered model. The other is based on the control of backstepping. Several simulation tests were done to see how the robot moved after the two control methods were used.